Sufficiency Economy: Demission of Social Capital Development to the Pace of Change in the 21st Century of Thailand - Paitoon Pimdee; Pornchai Jedaman; Kollawat Wang-Saorad; Nittayaporn Kinboon (My University, 2017)
Modernization brings a major shift into the development process in the society of Thailand.The phenomenon started from foreign powers authority, either in the form of knowledge or assistance came to the domination.Determining discourse to generate new meaning on the Sufficiency Economy is demanded for fully responding to modernization era.Does the modern development in globalization cause the impacts?This research aims to study the respondents' ideas towards Sufficiency Economy: demission of social capital development to pace of change in the 21 st Century of Thailand.This was a qualitative research using the semi-structure questionnaire plus triangular check from the documentary and participatory action learning (PAL) with the community leadership.The respondents were 240 persons from purposive sampling in three provinces of Thailand.The qualitative data were analyzed by using three main stages: data reduction, data organization, and data interpretation to conclusion.The results consisted of five themes: I) Minds Dimension including the mentally strong awareness and realization that good, the independence of thought and action, creativity generosity and compromise, II) Social and Economic Dimension including the buddy, to link a strong network, to have a careful planning in managing existing assets, to have a backup plan in immune system of the risks and alternatives, the value and development, III) Technology Dimension including the selection of what suits your needs, knowing to improve the environment and the reality, IV) Cultural Dimension including an intellectual development potential and the uniqueness, and V) Resources and Environment Dimension including the development and use to the appropriate values.
Keywords: Pace; Capital (architecture); Economic Growth and Fiscal Policies